Beyond "Lack of Political Will": Elaborating Political Economy Concept s to Advance "Thinking and Working Politically" Comment on "Health Cov erage and Financial Protection in Uganda: A Political Economy Perspect ive" - Ssennyonjo, Aloysius (International Journal of Health Policy and Management, 2022)
Political economy analysis (PEA) has been advanced as critical to unde rstanding the political dimensions of policy change processes. However , political economy (PE) is not a theory on its own but draws on sever al concepts. Nannini et al, in concert with other scholars, emphasise that politics is characterised by conflict, contestation and negotiati on over interests, ideas and power as various agents attempt to influe nce their context. This commentary reflects how Nannini et al wrestled with these PEA concepts - summarised in their conceptual framework us ed for PEA of the Ugandan case study on financial risk protection refo rms. The central premise is that a common understanding of the PEA con cepts (mainly structure-agency interactions, ideas, interests, institu tions and power) forms a basis for strategies to advance thinking and working politically. Consequently, I generate several insights into ho w we can promote politically informed approaches to designing, impleme nting and evaluating policy reforms and development efforts.